San Jose Well Pump Company Plant - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Several buildings belonging to the San Jose Well and Pumping Company. San Jose Well and Pump Company office is flanked by Turbine Pumps and Well Drilling buildings, with a building marked Well Casing to the far right. The sign on the Turbine Pumps building reads "pumping plants/pipe and fittings/pressure systems/special machinery". The sign on the Well Drilling building reads "well rigs/well tools/drillers supplies/welding". The Well Casing building advertises "tanks/smoke stacks/sheet steel/fabricators". A street sign identifies the location as Buena Vista Avenue.